(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This paper examines the scientific and methodological foundations of integrating innovative technologies into the independent learning process within higher education. It focuses on the transition toward student-centered paradigms, specifically within the context of the Republic of Uzbekistan’s strategic educational reforms. By analyzing Self-Regulated Learning (SRL) theories, the implementation of the HEMIS platform, and the impact of immersive tools like VR and AR, the study demonstrates how digital infrastructure scaffolds student autonomy. The research concludes with a five-stage methodological model and didactic requirements for effective technology-driven independent study.